S1 guideline on occupational skin products: protective creams, skin cleansers, skin care products (ICD 10: L23, L24) - short version - Fartasch, Manige; Diepgen, Thomas L.; Drexler, Hans; Elsner, Peter; John, Swen Malte; Schliemann, Sibylle (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Job-related hand dermatitis heads up the list of reported occupational diseases. So-called skin products - understood to mean protective creams, skin cleansers and skin care products - are used for the primary and secondary prevention of job- related hand dermatitis. In the interests of evidence-based medicine, the only preventive measures and/or occupational skin products that should be used are those whose potential uses and efficacy are underpinned by scientific research. To this end, the Arbeitsgemeinschaft für Berufs- und Umweltdermatologie e.V. (Working Group for Occupational and Environmental Dermatology, ABD) of the DDG (German Dermatological Society) and the Deutsche Gesellschaft für Arbeits- und Umweltmedizin (German Society for Occupational and Environmental Medicine, DGAUM) have summed up the latest scientific findings and recommendations in the updated guideline. The benefit of the combined application of protective creams and skin care products in the primary and secondary prevention of work-related contact dermatitis has been widely confirmed by recent clinical-epidemiological studies. The guideline clearly explains the necessity of demonstrating the efficacy of protective creams and cleansing products by means of in vivo methods in the sense of repetitive applications. Transferable standardised testing systems designed to examine the irritation potential and thus the compatibility of occupational skin cleansers and the reduction of irritation by protective skin creams have now been developed and validated by multicentre studies for skin protection creams and cleansers. The status of the current assessment of the safety of occupational skin products is also summarised.
EVALuna2:9727